Acute compartment syndrome. (June 2017) - Schmidt, Andrew H.
Abstract: Acute compartment syndrome is a well-known complication of tibial fractures, yet it remains difficult to diagnose and the only effective treatment is surgical fasciotomy. Delayed fasciotomy is the most important factor contributing to poor outcomes, and as a result, treatment is biased towards performing early fasciotomy. Current diagnosis of ACS is based on clinical findings and intramuscular pressure (IMP) measurement, and is targeted at identifying safe thresholds for when fasciotomy can be avoided. Since clinical findings are variable and difficult to quantify, measurement of IMP – ideally continuously – is the cornerstone of surgical decision – making. Numerous investigators are searching for less invasive and more direct measurements of tissue ischemia, including measurement of oxygenation, biomarkers, and even neurologic monitoring. This article provides a brief but thorough review of the current state of the art in compartment syndrome diagnosis and treatment.